KOMISI PEMLIHAN UMUM DAN HAK POLITIK PENYANDANG DISABILITAS OLEH KABUPATEN TEMANGGUNG DALAM PEMILIHAN BUPATI TEMANGGUNG TAHUN 2018 - Sari, Mega Pramitha; Astrika, Lusia (Journal of Politic and Government Studies, 2019)
This study discusses the dynamics of the process of fulfilling the political rights of persons with disabilities in the Temanggug regent election in 2018 by the Temanggung KPU. The lack of service for persons with disabilities in the Temanggung election by the KPU makes the political rights of disability in the election of Temanggung not maximally fulfilled.The purpose of this study is to describe and analyze the dynamics of the process of fulfilling the political rights of persons with disabilities by the KPU Temanggung in Temanggung Pilbup in 2018 and identify the inhibiting factors. The research method used is descriptive qualitative with data collection techniques through interviews and documentation. The theoretical framework used is the Concept of Disabled, Disabled and Disability, the Concept of Democracy and Election, and the Concept of Human Rights.The results of the study showed that in the Temanggung regent election on 2018, KPU Temanggung had not been maximized in providing programs that initiated the fulfillment of the political rights of disability, the equality for disabilities to play an active role in the election implementation was still hampered by educational requirements. However, KPU Temanggung has been tried to serve disability by adjusting the budget for disability needs, and committed to providing services to them despite the shortcomings. KPU Temanggung had also implemented two of the four strategies to support the creation of inclusive elections so that the political rights of disability can be fulfilled. Factors that inhibit the process of implementation are low disability education background, election organizers who lack understanding of SOPs, invalid data, lack of accessibility, and poor reference choices.KPU Temanggung has sought the implementation of the fulfillment of the political rights of disability in the 2018 election, even though it has not been maximized. Suggestions that can be made by the Temanggung Disdukcapil are recording the pick-up administration of the ball. For KPU Temanggung is to improve the disability database, interactive dialogue with disabilities, cooperation with election participants for socialization. And for those with disabilities, they must actively follow up on political information and not hide family members with disabilities.Keywords: KPU, political rights, persons with disabilities, regent elections